2015
DOI: 10.1038/sj.bdj.2015.559
|View full text |Cite
|
Sign up to set email alerts
|

Discover Dentistry: encouraging wider participation in dentistry using a massive open online course (MOOC)

Abstract: This paper describes how a relatively new style of online learning, a massive open online course, may be used to raise aspirations and widen participation in dental professions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 1 publication
3
22
3
3
Order By: Relevance
“…Although previous studies revealed that professional and educational pursuits for example are among principal motivators for MOOC learners (Stokes et al, 2015;Radford et al, 2015), these results seem to signal the importance of friendship in MOOCs and other learning environments. While Belanger and Thornton (2013) did find that MOOC learners were also motivated by social experience, this study reveals the effect friends have on MOOC enrollment.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…Although previous studies revealed that professional and educational pursuits for example are among principal motivators for MOOC learners (Stokes et al, 2015;Radford et al, 2015), these results seem to signal the importance of friendship in MOOCs and other learning environments. While Belanger and Thornton (2013) did find that MOOC learners were also motivated by social experience, this study reveals the effect friends have on MOOC enrollment.…”
Section: Discussioncontrasting
confidence: 39%
“…However, compared to other studies (Radford et al, 2015;Stokes, Towers, Jinks & Symington, 2015;Zhong et al, 2016), earning credits and the relationship with participants' program, which can be assimilated to educational pursuit in previous studies, are not as important as friends when it comes to stirring students to enroll into a MOOC. For instance, 53.7% were stimulated by the connection of the course to their program, but 79.5% did not enroll to earn credits.…”
Section: Employment Statusmentioning
confidence: 99%
“…There are studies which administered the survey before a MOOC was started. Such studies can be useful for understanding course participants' demographics [28], motivation for enrollment [26], [34]- [36], intended study behaviour [26], [36], [37], and pre-course attitudes [38]. Additionally, there are researchers who carried out the survey by the end of a MOOC.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, so-called xMOOC adopts a more traditional pedagogy and relies on a tutor-centered approach. In whatever way they are categorized, MOOCs are widely known to exhibit two core features; (1) open access where anyone can participate in an online course (Levy, 2011;Martin, 2012;Pappano, 2012;O'Prey, 2013;Chen, 2015;Bates, 2014;Czerniewicz, Deacon, Fife, Small & Walji, 2015;Terras & Ramsay, 2015;Conole, 2015;Robinson, Kerski, Long, Luo, DiBiase & Lee, 2015), and (2) scalability in which courses are designed to support an indefinite number of participants (Chen, 2013;Conole, 2015;Robinson et al, 2015;Stokes, Towers, Jinks & Symington, 2015;Agrawal, Kumar & Agrawal, 2015;Czerniewicz et al, 2015).…”
Section: Moocs For Cpdmentioning
confidence: 99%